PENGARUH FREE CASH FLOW, GOOD CORPORATE GOVERNANCE, KUALITAS AUDIT, DAN LEVERAGE TERHADAP MANAJEMEN LABA - Satiman, Mr (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
The bad impact of loss is bankruptcy and distrust. Therefore, a financial study is needed to find out many factor should be improved. The purpose of this research is to known the effect of free cash flow, good corporate governance, audit quality, and leverage on earning management. The research is analyzing description on quantitative approach.The data on this research is from one of webs governance at www.idx.co.id with the scope of research is manufacturing company, in the sector of basic industry and chemical. Population in this research is 60 sompany and the result is 9 sample company at one period. The range in this research start from 2012 ? 2017. The used Technic in this research is classic assumption test and multiple liniear regresion analysis. The result show both simultaneously variable independent has a effect with variable dependen, where variable independent in this research is free cash flow, good corporate governance, the audit quality, and leverage, a meanwhile the variable dependent is earning management. The result on this research, has been found it where the subvariable of free cash flow have a negative effect on earning manajemen, the others subvariable good corporate governance, the audit quality, and leverage has no effect on earning manajemen, for the simultaneously research between free cash flow, good corporate governance, the audit quality and leverage have a effect on earning Management